Implementing minimum nutritional guidelines for school meals in secondary schools in Wales: What are the challenges?. (2nd October 2019) - Addis, Samia
Abstract : Background: Minimum nutritional guidelines for school meals were introduced across the UK to address concerns about poor provision and rising childhood obesity but little evidence relates to the challenges associated with implementing guidelines within the school context. Aims: Using an implementation model, this paper reports a qualitative study of the views, experiences and challenges identified in respect of the implementation of minimum nutritional guidance (Appetite for Life) in secondary schools in Wales. Methods: Semi-structured interviews ( n =13) were undertaken with policy, local authority and school staff members in four schools within one local authority in Wales. Interviews were recorded and transcribed and analysis was underpinned by a framework approach. Findings: Members of staff welcomed the guidelines, noting the contribution to the health and wellbeing of pupils, however, they reported that meals were less popular and that take-up of school meals had reduced as pupils endeavoured to access banned foods elsewhere. Conclusions: The guidelines have implications for school meal uptake and contextual factors such as the built environment will influence the success of such policies.